2016
DOI: 10.1002/jctb.5151
|View full text |Cite
|
Sign up to set email alerts
|

Effective solvent extraction of La, Ce and Pr from hydrochloric acid with a novel extractant N,N-dihexyloxamic acid

Abstract: BACKGROUND For the first time, N,N‐dihexyloxamic acid (HA) has been developed to extract La, Ce and Pr from hydrochloric acid solution in present work. RESULTS La, Ce and Pr can be extracted by HA in the pH range 1.3 to 2.0 using heptane as diluent. The extraction order was La < Ce < Pr. The separation factors were calculated to be 1.8 for La/Ce and for Ce/Pr. Based on slope analysis, all the rare earths (REs) were loaded in the form of REsCl0.6A2.4(HA)0.6 that may be a statistical expression of a mixture of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Our previous research confirmed that chloride ions can interact with REs, causing chloride ions to compete with HA for Res. [34] This adverse effect reached saturation when the chloride ion concentration was 0.13 mol⋅L À 1 . According to the above results, the extracted complexes can be expressed as REs(A) 3 and the extracting process can be described as:…”
Section: Effect Of Ionic Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research confirmed that chloride ions can interact with REs, causing chloride ions to compete with HA for Res. [34] This adverse effect reached saturation when the chloride ion concentration was 0.13 mol⋅L À 1 . According to the above results, the extracted complexes can be expressed as REs(A) 3 and the extracting process can be described as:…”
Section: Effect Of Ionic Strengthmentioning
confidence: 99%
“…[28][29][30][31][32][33] Previously, we focused on the structure optimization of carboxylic acid extractant, and developed a novel type of extractant, namely N,N-dihexyloxamic acid, which is a medium strong acid and exhibits an excellent extraction ability than CA12. [34] Encouraged by this progress, we synthesized another interesting extractant, namely 2-(2-heptanoylphenoxy)acetic acid (HA), which is supposed to have better extraction capacity than CA12 without additional additives. The improvement of extraction capacity of HA can be attributed to the optimization of molecular structure and the 2-heptanoyl group in HA may strengthen the affinity of phenoxyacetic carboxylic acid group to REs.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of the impurities encountered in REE recovery, some of the leached Fe is also recovered as ammonium jarosite in the final REF product. To remove this impurity, the final product form is subjected to high temperature (250-500 • C) to decompose the ammonium jarosite [18][19][20][21] For solvent extraction and ion exchange, different cationic, anionic and solvating extractants such as di (2-ethyl-hexyl) phosphoric acid (D2EHPA), dialkyl phosphonic acid (Cyanex 272), 2-ethyl-hexyl phosphonic acid mono-2-ethyl-hexyl ester (PC 88A), neodecanoic acid (Versatic 10), tributyl phosphate (TBP), and tricaprylylmethylammonium chloride (Aliquat 336) have been reported for the separation of REEs from solution with D2EHPA being more commonly used with nitrate, sulfate, chloride and perchlorate solutions, PC 88A with chloride solutions, and TBP with nitrate solutions [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Interestingly, many of the same chemical types used as solvent extractants are also used in solid form as ion-exchange resins from the same type of leaching solutions [23,24,28,32].…”
Section: Introductionmentioning
confidence: 99%